Use of Biosimilar Granulocyte Colony-Stimulating Factor for Mobilization in Autologous and Allogeneic Hematopoietic Stem Cell Transplantation - Eplin, Dwight D.; Jackson, Anna D.; Smith, Austin M.; Salvig, Brent; Chinratanalab, Wichai; Savani, Bipin N. (Clinical hematology international, 2019)
The biologic medication filgrastim is approved by the Food and Drug Administration (FDA) to mobilize hematopoietic progenitor cells (HPCs) for collection by leukapheresis for autologous hematopoietic stem cell transplant (HSCT). The FDA-approved biologic tbo-filgrastim is currently used off-label for this indication in both autologous and allogeneic HSCT at the Tennessee Valley Healthcare System. The purpose of this review is to compare the efficacy of filgrastim and tbo-filgrastim for this indication. The primary outcomes were the proportion of autologous patients and allogeneic donors with a CD34+ count ≥15 × 10 3 cells/uL on day 4 of filgrastim or tbo-filgrastim mobilization. The secondary outcome was the use of plerixafor in the autologous population. A total of 469 subjects were identified for inclusion; 367 underwent mobilization for autologous HSCT and 102 for allogeneic HSCT donation. The primary outcome was achieved in 47.5% of patients who received filgrastim compared to 50.2% who received tbo-filgrastim in the autologous population ( p = 0.67). Among donors for allogeneic HSCT, there was no difference between those eligible for collection on day 4 of filgrastim or tbo-filgrastim administration (97.6% vs. 100%, p = 0.41). No significant difference was identified in the number of patients requiring plerixafor use in the autologous HSCT population. The use of the biosimilar tbo-filgrastim for mobilization in either autologous HSCT patients or allogeneic HSCT donors has comparable outcomes to that of the biotherapeutic reference product filgrastim at a reduced cost to the healthcare system.